Komunikasi Politik Pangan Lokal Di Provinsi Maluku - Risyart.A Far Far; Amiruddin Saleh (Jurnal Komunikasi Pembangunan, 2016)
Political communication becomes an important aspect in the process of development of the agricultural sector in the region, particularly within the framework of the national development program planning policies, decentralization and regional autonomy. Maluku region is one of the main areas of sago in Indonesia with a total area of about 53.866 ha sago. Sago as a food ingredient has a relatively high carbohydrate content of food than rice maize, cassava, and potatoes. In order to achieve food security, one of the efforts that can be done is to carry back towards the diversification of food production and food consumption are diverse, nutritionally balanced and safe, and most importantly is based on local resources. Maluku implement local food politics by creating a development strategy, namely, the acceleration of local food verified. The role of political communication is very important in delivering the policy concerning the public interest because it required extensive knowledge especially in the delivery of a process approach intended to be accepted by society. Food politics Moluccan government in addressing the issue of sago can be seen on the measures taken. Where, Maluku provincial government in 2011 has issued Local Regulation No. 10 Tahun 2011 on the Management and Preservation of Sagu (called Perda Sago) under which aims to guarantee the availability of sources of food-producing carbohydrates as stipulated in Article 3 of Regulation Sago is (Maluku Provincial Government 2011).